Comparative Assessment of Hemostasis Patients with Compensated and Decompensated Cirrhosis - Tugushev, Aliy S.; Cherkovska, Olga S. (British Journal of Healthcare and Medical Research, 2025)
We have studied the pro- and anticoagulant systems in patients with compensated and complicated course of the disease in dynamics. The presence of thrombophilia in patients with compensated course of liver cirrhosis, which may be one of the pathogenetic factors in the development of complications, and disseminated intravascular coagulation in patients with decompensated cirrhosis, which is a consequence of thrombophilia and the cause of hemorrhagic syndrome, has been shown. The aim: to give the comparative assessment of the state of hemostasis system in patients with liver cirrhosis with uncomplicated and complicated course of the disease. Materials and methods: The study involved 240 patients with liver cirrhosis hospitalized during 2017-2021. 190 patients were assigned to the group with complicated - decompensated course of cirrhosis: 123 had gastrointestinal bleeding, 67 had ascites. 62 patients died during the follow-up. 50 patients were referred to the group of patients with uncomplicated - compensated course of the disease. At the time of examination they had no specific complaints. Assessment of procoagulant link included the determination of the number of platelets, prothrombin index, activated partial thromboplastin time, fibrinogen, and activity of coagulation factor F VIII. Assessment of anticoagulant link included the determination of protein C activity. Additionally, markers of thrombosis were assessed by the level of fibrinogen "B" and D-dimer. Results: When assessing the hemostatic system in decompensated patients with liver cirrhosis, the indicators of the pro- and anticoagulant link at admission and in dynamics were changed within wide limits, both in the direction of hypo- and hypercoagulation, regardless of the complications nature. In compensated patients, the standard coagulogram did not differ from normal values. At the same time, the activity of coagulation factor FVIII in 65.2% of patients was at the upper limit of the parameters taken as the norm, and in 35.6% it exceeded the upper limit of the norm. The activity of anticoagulant protein C in plasma in 88.0% of patients with LC was 1.5 - 1.8 times lower than the lower limit taken as the norm. At the same time, a decrease in the number of platelets, prothrombin index, fibrinogen, and an increase in the APTT level characteristic of decompensated patients can be regarded as manifestation of disseminated intravascular coagulation syndrome. Confirmation of the presence of disseminated intravascular coagulation syndrome is an increase in the level of D-dimer in blood, which was observed in 75.0% -97.0% of patients upon admission, and in 90.0% -99.0% in dynamics among the deceased, regardless of the complications nature. Conclusions: In compensated patients with liver cirrhosis, the state of hemostasis during the natural course of the disease is characterized by imbalance in the direction of hypercoagulation, which is confirmed by a decrease in the activity of protein C against the background of normal or increased activity of the coagulation factor FVIII. Decompensated patients have DIC syndrome in varying degrees of severity, characterized by laboratory thrombocytopenia, a decrease in the prothrombin index, fibrinogen, an increase in APTT, the appearance of fibrin degradation products (D-dimer), which clinically determines the hemorrhagic syndrome in liver cirrhosis. Among the deceased patients, the content of D-dimer practically did not change over time, being increased in 90.0% of patients with bleeding and 99.0% with ascites.